Pitfalls in Bone Marrow Edema Interpretation on Dual-Energy CT: Challenges and Solutions - Yap, Jiawei Alexander; Ong, Yu Xuan Nicholas; Weber, Marc-André (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Bone marrow edema (BME) is a significant imaging finding in musculoskeletal and emergency radiology, often associated with trauma or nontraumatic etiologies such as inflammation, infection, or neoplasms. Magnetic resonance imaging (MRI) remains the gold standard for BME evaluation. However, dual-energy CT (DECT) has emerged as a valuable alternative due to its faster acquisition times, lower costs, and more rapid access in emergency settings (when compared with MRI), facilitating timely decision-making when MRI is impractical or contraindicated. Despite its benefits, accurate interpretation of BME on DECT requires careful understanding of its limitations and potential pitfalls. This article addresses the technical and clinical challenges in DECT-based BME assessment and proposes strategies to enhance diagnostic accuracy.A review of the literature was performed by searching the PubMed and ScienceDirect databases, using the keywords (“DECT” or “Dual-Energy”) and (“BME” or “bone marrow edema”) and (“musculoskeletal” or “bone” or “skeleton”) for the title and abstract query. The inclusion criteria were scientific papers presented in the English language. Exclusion criteria included articles which had no relevant focus on BME and case reports. Of the 168 articles initially identified, 75 were deemed relevant and were reviewed in detail. Insight from this literature search and the authorsʼ clinical experience forms the basis of this review, highlighting key pitfalls and strategies for accurate BME interpretation.DECT provides significant advantages for detecting BME, such as material-specific color overlays and high anatomical correlation. However, key pitfalls include the misinterpretation of artifacts, difficulties in cases of severe displacement or sclerosis, and challenges posed by imaging artifacts in large-sized patients or those with metallic implants. Radiologists can improve diagnostic accuracy by understanding the limitations and pitfalls of DECT, and by adopting the solutions outlined in the article to optimize its use.
Keywords: bone marrow edema; BME; dual-energy CT; pitfalls